Correlation-Based Analysis and Generation of Multiple Spike Trains Using Hawkes Models with an Exogenous Input - Krumin, Michael; Reutsky, Inna; Shoham, Shy (Frontiers in Computational Neuroscience, 2010)
The correlation structure of neural activity is believed to play a major role in the encoding and possibly the decoding of information in neural populations. Recently, several methods were developed for exactly controlling the correlation structure of multi-channel synthetic spike trains (Brette, 2009; Krumin & Shoham, 2009; Macke, et al., 2009; Gutnisky & Josic, 2010; Tchumatchenko, et al., 2010) and, in a related work, correlation based analysis of spike trains was used for blind identification of single-neuron models (Krumin, et al., 2010), for identifying compact auto-regressive models for multi-channel spike trains, and for facilitating their causal network analysis (Krumin & Shoham, 2010). However, the diversity of correlation structures that can be explained by the feed-forward, non-recurrent, generative models used in these studies is limited. Hence, methods based on such models occasionally fail when analyzing correlation structures that are observed in neural activity. Here, we extend this framework by deriving closed-form expressions for the correlation structure of a more powerful multivariate self- and mutually-exciting Hawkes model class that is driven by exogenous non-negative inputs. We demonstrate that the resulting Linear-Nonlinear-Hawkes (LNH) framework is capable of capturing the dynamics of spike trains with a generally richer and more biologically relevant multi-correlation structure, and can be used to accurately estimate the Hawkes kernels or the correlation structure of external inputs in both simulated and real spike trains (recorded from visually stimulated mouse retinal ganglion cells). We conclude by discussing the method’s limitations and the broader significance of strengthening the links between neural spike train analysis and classical system identification.